2022
DOI: 10.1101/2022.04.27.489466
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coordination between ECM and cell-cell adhesion regulates the development of islet aggregation, architecture, and functional maturation

Abstract: SUMMARYPancreatic islets are 3-dimensional aggregates consisting of unique cellular composition, cell-to-cell contacts, and interactions with blood vessels. Islet cell aggregation is essential for proper endocrine cell function; however, it remains unclear how developing islets establish aggregation. By combining genetic animal models, imaging tools, and gene expression profiling, we demonstrate that the formation of islet aggregates is regulated by extracellular matrix signaling and cell-cell adhesion. Islet … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…Furthermore, FGF9 and FGF10 , genes recently shown to be involved in pancreatic development 59 and previously known to be important for neuronal development and maturation 60 play a role in the GO pathway developmental growth for the acinar cell cluster. In the endocrine cluster, the GO pathway neuron projection morphogenesis is characterised by Pax6 , a gene responsible for development of the pancreas and other neuroectodermal structures, 61 ISL1 , a gene important for beta cell function, 62 and ITGB1 , a gene coding for an integrin critical for islet cell development in the pancreas 63 and for neuronal cell migration 64 . ADM GO enrichment includes cell–cell junctions and adhesions, representing the transition of acinar cells to a more ductal‐like phenotype 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, FGF9 and FGF10 , genes recently shown to be involved in pancreatic development 59 and previously known to be important for neuronal development and maturation 60 play a role in the GO pathway developmental growth for the acinar cell cluster. In the endocrine cluster, the GO pathway neuron projection morphogenesis is characterised by Pax6 , a gene responsible for development of the pancreas and other neuroectodermal structures, 61 ISL1 , a gene important for beta cell function, 62 and ITGB1 , a gene coding for an integrin critical for islet cell development in the pancreas 63 and for neuronal cell migration 64 . ADM GO enrichment includes cell–cell junctions and adhesions, representing the transition of acinar cells to a more ductal‐like phenotype 15 .…”
Section: Resultsmentioning
confidence: 99%
“…It is also involved in the EMT‐mediated metabolic reprogramming of cancer cells. Studies reported a reduced expression of matured ITGB1 in mesenchymal phenotype in comparison to epithelial, thereby causing detachment from ECM 23 . This detachment from ECM induces the lysosomal degradation of the ITGB1/IR complex and metabolic reprogramming of aerobic glycolysis to FA oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Research continues to explore the essential role of extracellular matrix (ECM) proteins in regulating islet architecture, including supplementing Matrigel with key ECM factors (Tixi et al, 2022;Tremmel et al, 2022). Slit is the canonical ligand for Robo receptors, and has also been 9…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, islets derived from stem cells function better when induced to form mature architecture (Balboa et al, 2022). Research continues to explore the essential role of extracellular matrix (ECM) proteins in regulating islet architecture, including supplementing Matrigel with key ECM factors (Tixi et al, 2022; Tremmel et al, 2022). Slit is the canonical ligand for Robo receptors, and has also been shown to impact islet formation in developing mice (Gilbert et al, 2020).…”
Section: Discussionmentioning
confidence: 99%